Immigrant entrepreneurs in the U.S.: Firm performance based on entrepreneurial competencies - Honghua Li; Yemisi Awotoye; Robert P. Singh (Economies, 2023)
Although immigrants represent a sizeable and growing portion of the total U.S. population and immigrant entrepreneurs play an important role in the U.S. economy, they remain relatively understudied within the literature. Existing research suggests that immigrants are more likely to start a business than non-immigrants in the U.S. and face unique challenges while doing so. This paper attempts to contribute to the existing literature by examining the impact of entrepreneurial competencies of immigrant entrepreneurs on their firms' performance. Given that entrepreneurial success, performance, and growth depend heavily on entrepreneurial competencies, we develop a conceptual discussion and three propositions indicating that immigrant-owned firm performance is influenced by three specific competencies held by immigrant entrepreneurs: proficiency in the host country's language, knowledge about the host country, and cultural intelligence. Following a review of the literature and the development of the propositions, we discuss implications, limitations, and future research directions for researchers and practitioners.
Keywords: 330; immigrant entrepreneurs; entrepreneurial competencies; firm performance